Exploring the Relationship Between SGLT2 Inhibitors and Glycosuria: A Cross- Sectional Analysis (Medical Forum Monthly, 2024)
Objective: In order to explore how type and dose of the SGLT2 inhibitors affects the level of urine sugar in type 2 diabetes mellitus patients.Study Design: Cross-sectional StudyPlace and Duration of Study: This study was conducted at the Department of Medicine Khyber Girls Medical College Peshawar from Jan 2023 to Dec 2023.Methods: A cross-sectional Study was used on 100 patients diagnosed with type 2 diabetic mellitus. Patients were on SGLT2 inhibitors for at least 6 months before they were seen by their GP and offered glycaemic monitoring. Urine glucose was also estimated, and correlation with SGLT2 inhibitor dosage and clinical data were then compared. Descriptive analysis in the form of mean and standard deviation and inferential analysis through p value have been used using SPSS software.Results: The Mean quantity of glucose in urine was 45 ± 8 g/day. As compared with patients on low doses of SGLT2 inhibitors, the proportion of patients with increased glycosuria was significantly (p < 0.01) higher in patients on high doses of the latter. Standard deviation for glycosuria over the study population was 7.5 g/day with an average age of patients 54 ± 6.8 years. Elevated amounts of glucose in the urine were also positively associated with the daily dose of the SGLT2 inhibitor in stable conditions: the correlation coefficient was 0.80 (p < 0.001) for patients with baseline glucose levels above 180 mg/dLConclusion: SGLT2 inhibitors have also been seen to increase glycosuria in patients being candesartan for type 2 diabetes with this being enhanced by higher doses was found. The results offer evidence for their role in improving glycemic management and reducing hyperglycemia, offering guidance on dose optimization in clinical settings.